Dinosaurs in 2D Animation: An Innovative Learning Strategy to Improve Natural History Comprehension Skills in Indonesia - Pratama, Jimmy; Adnas, Diny Anggriani; Pratama, Carlos Pingsen (Jurnal Pendidikan Multimedia (Edsence), 2024)
This research aims to develop 2D animation-based learning media about dinosaurs to enrich students' understanding of natural history. The development method used is MDLC (Multimedia Development Life Cycle) which includes six stages, namely concept, design, material collection, creation, testing, and distribution. The testing process involved alpha and beta tests to assess the quality of the animation in terms of visual and audio, as well as the accuracy of the information. The response from the audience was overall positive, with 85% stating that the animation made it easier to understand the material and added to their knowledge about dinosaurs. In addition, 90% of respondents rated the information conveyed in this animated video as accurate and reliable. The results show that 2D animation is not only able to attract attention, but also be an effective medium in conveying complex learning materials in a simple manner. Recommendations for further research are to add interactive elements and explore the use of 3D animation or augmented reality (AR) technology for a more immersive learning experience.